(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Allergic conjunctivitis is commonly complicated by secondary dry eye syndrome that substantially affects the quality of life of patients and requires a comprehensive approach to treatment. Purpose: To improve treatment of dry eye patients with allergic conjunctivitis through the use of artificial tears. Material and Methods: Fifty-six patients with acute allergic conjunctivitis complicated by secondary dry eye syndrome were included in the study. The main group, but not the control group, received artificial tears as adjunct to basic therapy. A comprehensive analysis included a study of clinical symptoms, status of the tear complex and meibomian glands. Results: In addition to improvements in scores of subjective symptom questionnaire, and Schirmer test and tear film break up time (TFBUT) measurements, more apparent improvements in signs of disease were found in patients who received artificial tears as an adjunct to basic therapy beginning from day 10. The most severe meibographic evidence of morphological defects in gland ducts was seen in the papillary and follicular forms of conjunctivitis. Conclusion: Comprehensive therapy with introduction of artificial tears as an adjunct at day 10 of basic treatment is a reasonable and pathogenetically substantiated corrective treatment for poor tear film function in the acute phase of allergic conjunctivitis.